Indoloquinoline Alkaloids as Antimalarials: Advances, Challenges, and Opportunities - Parvatkar, Prakash T.; Diagne, Khaly; Zhao, Yingzhao; Manetsch, Roman (ChemMedChem, 2024)
Malaria infections affect almost half of the world‘s population, with over 200 million cases reported annually. Cryptolepis sanguinolenta, a plant native to West Africa, has long been used across various regions of Africa for malaria treatment. Chemical analysis has revealed that the plant is abundant in indoloquinolines, which have been shown to possess antimalarial properties. Cryptolepine, neocryptolepine, and isocryptolepine are well‐studied indoloquinoline alkaloids known for their potent antimalarial activity. However, their structural rigidity and associated cellular toxicity are major drawbacks for preclinical development. This review focuses on the potential of indoloquinoline alkaloids (cryptolepine, neocryptolepine, and isocryptolepine) as scaffolds in drug discovery. The article delves into their antimalarial effects in vitro and in vivo, as well as their proposed mechanisms of action and structure‐activity relationship studies. Several studies aim to improve these leads by reducing cytotoxicity while preserving or enhancing antimalarial activity and gaining insights into their mechanisms of action. These investigations highlight the potential of indoloquinolines as a scaffold for developing new antimalarial drugs. Extracts from the plant C. sanguinolenta and the isolated indoloquinoline alkaloids have been found to possess potent antimalarial activities, in vitro and in vivo, against various strains of P. falciparum. Structure‐activity relationship studies identified more potent analogs. Furthermore, these indoloquinolines exhibit a synergistic effect when combined with other antimalarial drugs.